Determinants of employment in the Platinum mining industry in South Africa - Khoza, Nyiko (My University, 2017)
The study intends to investigate the determinants of employment in the platinum mining industry in South Africa. Employment levels decreased dramatically in the platinum mining industry in South Africa. This is due to decrease in export demand for platinum, high operating cost, labour unrest, low levels of production and other determinants of employment. The specific objective of the study is to determine the nexus between employment, output, domestic demand and export demand. Annual time series data covering the period between 1992-2013 was used. The study employed the Vector Error Correction Model approach. Johansen Cointegration test results confirmed the existence of a long run relationship amongst variables under investigation. Export demand and output are found to be positively related with employment. The speed of adjustment to equilibrium is -0.283202. Impulse response functions and variance decomposition are also generated to explain the response to shock amongst variables. The results of the study vindicate that the platinum mining industry should implement policies and strategies to increase output which will lead to higher levels of employment as well as economic growth. In addition, government should also create a conducive environment to enable the industry to expand and the industry should also intensify its export drive, these findings are envisaged to contribute significantly to the existing but limited literature on the subject under investigation.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2017
Keywords: Employment; Domestic demand; Export demand; VECM; Johansen Cointegration test; Impulse response; Employment.; Mines and mineral resources; Platinum mines and mining